Global trends in surgical approach to neonatal brachial plexus palsy: a systematic review - Levidy, Michael F.; Azer, Amanda; Shafei, Jasmine; Srinivasan, Nivetha; Mahajan, Jasmine; Gupta, Shivani; Abdelmalek, George; Pant, Krittika; Jain, Kunj; Shah, Yash; Zheng, Zheshi; Chuieng-Yi Lu, Johnny; et al. (Frontiers in Surgery, 2025)
Background: We analyzed trends in age at surgery and surgical approach over time and geography.Methods: We performed a systematic review according PRISMA-IPD guidelines to include individual patient data. Collected data included: age at surgery, location of surgery, and surgical approach. Surgical approach was independently categorized as: exploration of the brachial plexus (EBP) or nerve transfer without root exploration (NTwoRE). EBP was defined as exploring brachial plexus in the supraclavicular fossa and applying a choice of coaptation procedures. NTwoRE included those sourcing donor nerves from, or entirely occurring outside of the plexus without exploring the root of brachial plexus.Results: Regression analysis of age at surgery 1985-2020 showed that age at BPBI surgery is rising. (p<.05) Surgery was performed at a younger age in patients from Europe (7.06 ± 7.77 months) and Asia (7.58 ± 5.33 months) than those from North America (10.44 ± 5.01 months) and South America (14.71 ± 4.53 months). (p<0.05). NTwoRE were more common in North America (37%) and least common in Europe (12%). Age at EBP was 7.2 ± 5.77 months; age at NTwoRE was 15.85 ± 13.18 months. (p < .05) incidence of NTwoRE is increasing time.Conclusions: Age at NBPP surgery is increasing over time. Regional differences exist in age at NBPP surgery. Approaches to NBPP surgery that avoid exploration of BP roots are becoming more popular. Age at EBP is lower than age at NTwoRE.